Chick TV : antiheroines and time unbound - Levy, Yael (College teacher) (Television series (Syracuse, N.Y.), 2022)
"Drawing on the potential of both temporality and antiheroinism to invoke feminist resistance, this research suggests a correlation between televisual temporality and antiheroinism in early 2000s US television drama series, examines that correlation, and explores the feminist politics of these two narrative apparatuses"--